Preparation method of liquid-like coating based on dynamic phase separation

A MO-Si covalent cross-linked network was constructed on a flexible substrate through a dynamic phase separation method, which solved the problems of mechanical strength, optical transparency and preparation complexity of liquid-like coatings, achieved high hardness, low liquid adhesion and wear resistance, and is suitable for flexible electronic and photovoltaic devices.

CN120682719AActive Publication Date: 2025-09-23BEIJING INSTITUTE OF GRAPHIC COMMUNICATION
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510809535.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2025-09-23
Estimated Expiration
2045-06-17

AI Technical Summary

Technical Problem

Existing liquid-like coatings have difficulty in maintaining dynamic surface properties while balancing mechanical strength, thermal stability, and optical transparency. In addition, the preparation process is complex, the cost is high, and there is a high risk of failure in the use environment.

Method used

A dynamic phase separation method is used to form a MO-Si covalent cross-linked network on a flexible substrate through silicone resin, hydroxyl-terminated linear PDMS and metal coupling agent. The PDMS content is controlled within an extremely low range. Combined with solvent-induced phase separation and thermal curing treatment, a hard-flexible coating structure is constructed.

Benefits of technology

It achieves high hardness, low liquid adhesion, excellent optical transparency and wear resistance, is suitable for flexible electronic devices and photovoltaic devices, has good anti-fouling properties and thermal stability, is suitable for large-area spraying, and reduces preparation complexity and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120682719A_ABST
    Figure CN120682719A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a liquid-like coating based on dynamic phase separation, and belongs to the technical field of functional surface coatings, and the specific scheme comprises the following steps: step 1, adding organic silicon resin and hydroxyl-terminated linear PDMS into a volatile solvent, and treating by a homogenizer and an ultrasonic crusher to form an incompletely compatible mixed system; step 2, slowly dropwise adding a metal coupling agent into the mixed system, and stirring to enable the metal coupling agent and an active group of organic silicon resin to be subjected to a pre-crosslinking reaction, so as to obtain a coating solution; and 3, the surface of a flexible substrate is coated with the coating liquid, the coating liquid is left to stand to evaporate a solvent, phase separation disappears, thermocuring treatment is conducted on the flexible substrate, organic silicon resin and the tail end of PDMS are crosslinked, M-O-Si structure construction is completed, a liquid-like coating is obtained, and M is a metal element of a metal coupling agent. According to the invention, high hardness and low liquid adhesion are realized at the same time, and the problem that liquid repellency and mechanical properties of a coating are difficult to consider at the same time is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional surface coatings, and specifically relates to a method for preparing a liquid-like coating based on dynamic phase separation. The liquid coating has liquid-like surface properties, is anti-fouling and wear-resistant, and is suitable for flexible electronic devices and photovoltaic devices. Background Art

[0002] Currently, liquid repellent surface coatings are widely used in flexible electronics, photovoltaic devices, display modules and other fields to achieve anti-fouling, anti-fingerprint, dust-proof and improve device durability. Although traditional super-hydrophobic coatings have good water repellency, they rely on micro-nano structures and have poor mechanical stability, which can easily fail in friction or impact. [1] Although slippery liquid infused porous surfaces (SLIPS) can achieve excellent lubricity and anti-fouling properties, the injected liquid (such as lubricating oil) it relies on has problems such as loss, migration and contamination. [2] , it is difficult to apply it stably for a long time.

[0003] In order to avoid the loss of liquid components, some studies have proposed to construct liquid-like coatings by covalently grafting low surface energy polymer segments such as polydimethylsiloxane (PDMS) to the surface of solid substrates. [3] . This type of coating performs well in terms of contact angle hysteresis, lubricity and liquid repellency. When the content is too high, the degree of cross-linking of the coating will be reduced, further affecting the hardness and wear resistance of the coating. At the same time, high PDMS content may also lead to problems such as uneven phase separation and increased optical haze. In addition, in order to improve the hardness, some studies have introduced POSS (polyhedral oligomeric silsesquioxane) or multifunctional cross-linkers to enhance the mechanical properties of the coating, but this often involves complex synthesis steps or a high proportion of inorganic additives, which increases the process complexity and preparation cost.

[0004] Therefore, how to improve the mechanical strength, thermal stability, optical transparency and industrial preparation capability of the coating while maintaining the "liquid-like" dynamic surface properties remains a difficult problem that needs to be urgently solved in current liquid-like coating technology.

[0005] [1] Chen, F., Wang, Y., Tian, ​​Y., Zhang, D., Song, J., Crick, CR, Carmalt, CJ, Parkin, IP, and Lu, Y. (2022). Robust and durable liquid-repellent surfaces. Chemical Society Reviews, 51, 8476–8583.

[0006] [2] Zang, X., Ni, Y., Wang, Q., Cheng, Y., Huang, J., Cao,

[0007] [3] Hu, Z., Chu, F., Shan, H., Wu, X., Dong, Z., and Wang, R. (2024). Understanding and utilizing droplet impact on superhydrophobic surfaces: phenomena, mechanisms, regulations, applications, and beyond. AdvancedMaterials, 36, 2310177. Summary of the Invention

[0008] The main technical problems of liquid-like coatings in the existing technology are:

[0009] The problem of balancing liquid adhesion and mechanical strength: Existing liquid-like coatings usually require a higher content of polydimethylsiloxane (PDMS) to achieve dynamic wettability and low contact angle hysteresis (CAH < 2°), but a high PDMS content will significantly reduce the hardness and wear resistance of the coating, making it unsuitable for long-term protection requirements of flexible devices.

[0010] Phase separation leads to reduced optical transparency and structural stability of the coating: During the coating preparation process, PDMS has poor compatibility with the resin matrix and is prone to form a micron-scale PDMS-enriched structure, resulting in increased optical haze and mechanical degradation.

[0011] Minor technical issues:

[0012] The existing reinforcement methods are complex to prepare and have high costs: To improve the strength of the coating, some studies have introduced high-rigidity components such as POSS or constructed complex interpenetrating networks. Although effective, this increases the synthesis steps and material costs, which is not conducive to industrial applications.

[0013] The problem of high failure risk of coatings in complex usage environments: Existing coatings are prone to surface structure damage, loss of anti-fouling function or device performance degradation when subjected to stress conditions such as bending, wiping, high temperature or dust pollution.

[0014] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0015] A method for preparing a liquid-like coating based on dynamic phase separation comprises the following steps:

[0016] Step 1: Add the silicone resin and hydroxyl-terminated linear PDMS to a volatile solvent, and process them sequentially through a homogenizer and an ultrasonic crusher (40kHz, 1-15min) at room temperature to disperse the PDMS into small liquids, forming an incompletely compatible mixed system and inducing dynamic phase separation;

[0017] Step 2: slowly dropwise add the metal coupling agent to the above mixed system and continue stirring for 0.1-1h to allow it to undergo a pre-crosslinking reaction with the active groups of the silicone resin to obtain a coating solution;

[0018] Step 3: Evenly apply the coating liquid to the surface of a flexible substrate using screen printing, doctor blade coating, or spraying, let it stand at room temperature for 5-30 minutes to slowly evaporate the solvent and eliminate phase separation, and then perform a thermal curing treatment to crosslink the silicone resin and the PDMS ends and complete the MO-Si structure to obtain a liquid-like coating, where M is the metal element of the metal coupling agent. Preferably, the flexible substrate is a PET film or a PI film.

[0019] Furthermore, by weight, the silicone resin comprises 50-80% by weight of the coating solution, the hydroxyl-terminated linear PDMS comprises 0.5-1.5% by weight of the coating solution, the metal coupling agent comprises 1.0-5.0% by weight of the coating solution, and the volatile solvent comprises 15-45% by weight of the coating solution. When the linear PDMS content is controlled within an extremely low range (0.5–1.5% by weight), a slip layer can be formed on the surface without affecting the coating's structural stability or optical properties.

[0020] Furthermore, the organic silicone resin is a methoxysiloxane intermediate (MS), which is used to construct a cross-linked skeleton.

[0021] Furthermore, the molecular weight of the hydroxyl-terminated linear PDMS is 1000-100000 g / mol, and is used to construct a liquid-like dynamic interface.

[0022] Furthermore, the metal coupling agent includes a combination of one or more of a titanate coupling agent, an aluminate coupling agent, and a zirconate coupling agent; providing an M–O–Si structure to achieve “hard-flexible” synergistic enhancement.

[0023] Furthermore, the titanate coupling agent includes a combination of one or more of tetrabutyl titanate, isopropyl titanate and isooctyl titanate, the aluminate coupling agent includes a combination of one or more of isopropyl aluminate and butyl aluminate, and the zirconate coupling agent includes isopropyl zirconate.

[0024] Furthermore, the volatile solvent is a weak polar solvent, including anhydrous ethanol, isopropanol, methanol or low polar esters. Preferably, the low polar ester is ethyl acetate, which is used to induce dynamic phase separation.

[0025] Furthermore, in step three, the thickness of the liquid-like coating is 1-100µm.

[0026] Furthermore, in step three, the temperature of the heat curing treatment is 25-200° C., and the time is 0.1-20 hours.

[0027] According to actual needs, a surface additive or UV stabilizer accounting for 0-2 wt% of the mass fraction of the coating liquid is added in step 1 or step 2 to improve the anti-pollution or light stability performance.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. This invention achieves both high hardness and low liquid adhesion, resolving the challenge of balancing liquid repellency and mechanical properties in coatings. By utilizing a covalently crosslinked M–O–Si network to create a "hard-flexible" framework, the coating achieves a hardness exceeding 9H (ASTM D3363 standard) with a PDMS content as low as 0.5wt%, achieving a nanoindentation hardness 2.5 times that of a typical PET substrate (H = 0.53 GPa). Furthermore, the coating exhibits a surface contact angle hysteresis (CAH) of less than 2°, allowing both water and oil droplets (such as hexadecane) to slide off quickly, demonstrating excellent broad-spectrum anti-fouling properties.

[0030] 2. High optical transparency solves the problem of "whitening or increased haze of the coating caused by phase separation": the light transmittance of the coating remains above 90% in the range of 400-800nm, and the surface roughness is only 0.7nm (measured by AFM). There is no obvious phase separation structure or micro-nano agglomeration, making it suitable for fields with high requirements for visual transparency, such as display screens and optoelectronic devices.

[0031] 3. Excellent wear resistance and long-term anti-fouling properties solve the problem of "anti-fouling effect rapidly decays with use and wear": after 500 steel wool friction treatments (13kPa pressure), the CAH value of the coating remains below 10°, and the fingerprint liquid residue rate is less than 20%, which is far better than the unprotected PET surface (residual rate >60%), showing excellent wipe resistance, anti-fingerprint and anti-graffiti properties.

[0032] 4. Improved high-temperature resistance solves the problem of "poor thermal stability of flexible coatings": Thermogravimetric analysis shows that the coating of the present invention still retains 85.8wt% of its mass at 800°C, which is much higher than the thermal stability level of conventional polymer substrates such as PET, and is suitable for high-temperature exposure environments such as photovoltaic modules.

[0033] 5. The process is simple and can be sprayed to adapt to large-area flexible substrates, solving the problem of "incompatibility between complex processes and large-scale preparation": the present invention adopts conventional mechanical stirring and spray curing processes, does not require high-energy auxiliary equipment, and can form a uniform coating on a 0.5m×10m flexible PET film, with good scale and industrial transformation potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of contact angle hysteresis (CAH) of water and hexadecane droplets on the coating surface;

[0035] Figure 2 are the nanoindentation curves of the coating and PET film prepared in Example 1;

[0036] Figure 3 is the thermogravimetric curve of the coating and PET film prepared in Example 1;

[0037] Figure 4 is the UV-visible light transmittance curve of the coating prepared in Example 1;

[0038] Figure 5 This is a picture of a coating prepared by large-area spraying using the process of Example 1;

[0039] Figure 6 Schematic diagram of the contact angle hysteresis (CAH) of water and hexadecane after the coating in Example 1 is rubbed with steel wool. DETAILED DESCRIPTION

[0040] The technical solutions of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0041] Example 1:

[0042] A method for preparing a liquid-like coating based on dynamic phase separation comprises the following steps:

[0043] Silicone resin (60 wt%) and hydroxyl-terminated linear PDMS (0.5 wt%) were added to ethanol (36.5 wt%) and dispersed using a homogenizer (10,000 rpm, 10 min) and an ultrasonicator (40 kHz, 5 min) at room temperature to disperse the PDMS into small liquids, forming an incompletely compatible mixed system and inducing dynamic phase separation.

[0044] Slowly add the coupling agent tetrabutyl titanate (3 wt %) to the above mixed system and continue stirring and reacting for 0.5 h to cause a pre-crosslinking reaction between the coupling agent and the silanol and hydroxyl functional groups of the silicone resin to obtain a coating solution.

[0045] The obtained coating liquid was evenly coated on the PET film on the surface of the flexible substrate by spraying, and the coating thickness was controlled to be about 20µm;

[0046] The solvent was slowly evaporated at room temperature for 20 minutes, and the phase separation disappeared. The resulting mixture was then thermally cured at 120°C for 60 minutes to cross-link the silicone resin with the PDMS ends and complete the Ti–O–Si structure to obtain a liquid-like coating (SLC).

[0047] Example 2

[0048] The difference from Example 1 is that the hydroxyl-terminated linear PDMS accounts for 1 wt % of the coating solution, the silicone resin accounts for 59.5 wt % of the coating solution, and the remaining steps are the same as Example 1.

[0049] Example 3

[0050] The difference from Example 1 is that the hydroxyl-terminated linear PDMS accounts for 1.5 wt % of the coating solution, the silicone resin accounts for 59 wt % of the coating solution, and the remaining steps are the same as Example 1.

[0051] Example 4:

[0052] A method for preparing a liquid-like coating based on dynamic phase separation comprises the following steps:

[0053] Silicone resin (60 wt%) and hydroxyl-terminated linear PDMS (0.2 wt%) were added to isopropyl alcohol (36.8 wt%). The mixture was first homogenized (10,000 rpm, 10 min) at room temperature and then dispersed using an ultrasonicator (40 kHz, 5 min) to disperse the PDMS into small liquids, resulting in an incompletely compatible uniform dispersion system and inducing dynamic phase separation.

[0054] Subsequently, 3 wt% of isopropyl zirconate was slowly added dropwise to the dispersion system as a metal coupling agent, and the reaction was continuously stirred for 30 minutes to promote the coupling agent to form a Zr–O–Si cross-linked structure with the active silanol or hydroxyl functional groups of the silicone resin in the system to obtain a coating liquid.

[0055] The obtained coating liquid was evenly coated on the surface of the flexible PET substrate by spraying, and the wet film thickness was controlled to be about 10 μm to ensure the integrity of the film layer.

[0056] After coating, the film was left to stand at room temperature for 15 minutes until the phase separation disappeared. The sample was then placed in an oven and thermally cured at 100°C for 40 minutes to complete the cross-linking and curing process, ultimately obtaining a liquid-like coating.

[0057] Example 5:

[0058] A method for preparing a liquid-like coating based on dynamic phase separation comprises the following steps:

[0059] Silicone resin (70 wt%) and hydroxyl-terminated linear PDMS (1 wt%) were added to anhydrous ethanol (26 wt%) and dispersed in a homogenizer (10,000 rpm, 10 min) and an ultrasonic crusher (40 kHz, 5 min) at room temperature to disperse the PDMS into small liquids, forming an incompletely compatible mixed system and inducing dynamic phase separation behavior.

[0060] Tetrabutyl titanate (3 wt%) was slowly added dropwise to the above-mentioned mixed system as a coupling agent, and the mixture was stirred and reacted for 30 minutes to promote pre-crosslinking between the coupling agent and the silanol or hydroxyl functional groups in the silicone resin to form an initial Ti–O–Si crosslinked structure to obtain a coating solution.

[0061] The obtained coating liquid was evenly coated on the surface of the flexible PET film by spraying, and the wet film thickness was controlled to be approximately 20 μm to ensure that the subsequent film formation was uniform and continuous.

[0062] The solvent was slowly evaporated at room temperature for 20 minutes, and the phase separation disappeared. The coating was then thermally cured at 120°C for 60 minutes to cross-link the silicone resin with the PDMS ends and complete the Ti–O–Si structure to obtain a liquid-like coating.

[0063] Comparative Example 1

[0064] The difference from Example 1 is that the hydroxyl-terminated linear PDMS accounts for 0.2 wt % of the coating solution, the silicone resin accounts for 60.3 wt % of the coating solution, and the remaining steps are the same as Example 1.

[0065] Comparative Example 2

[0066] The difference from Example 1 is that the hydroxyl-terminated linear PDMS accounts for 2 wt % of the coating solution, the silicone resin accounts for 58.5 wt % of the coating solution, and the remaining steps are the same as Example 1.

[0067] List of main performance indicators of the liquid-like coating prepared in Example 1:

[0068]

[0069] By using the component ratio and process path in Example 1, it is possible to achieve: a PDMS-rich layer is formed on the coating surface, providing an ultra-low contact angle hysteresis (<2°), see Figure 1 As the PDMS content increases, the contact angle hysteresis (CAH) of water droplets and hexadecane droplets (5 μL) shows a trend of first decreasing and then increasing. When the PDMS content is 0.5 wt%, the CAH of water droplets and hexadecane droplets is the smallest, and the lyophobicity of the coating is optimal at this time. The introduction of the Ti–O–Si cross-linked network significantly improves the hardness of the coating (see Figure 2 ) and thermal stability (heat resistant up to 800°C, see Figure 3 ); coating light transmittance> 90%, maintaining the display performance of flexible devices, see Figure 4 ; Spraying has strong adaptability and is suitable for large-area flexible substrates (>0.5m×10m), see Figure 5 ; After 500 times of steel wool wear, it still maintains excellent anti-fouling performance, see Figure 6 .

[0070] This paper proposes a method for preparing a liquid-like coating based on a solvent-induced dynamic phase separation mechanism. By controlling the aggregation-dissipation behavior between the polymer PDMS and a low-polarity solvent, a surface-enriched PDMS brush structure is achieved. Furthermore, a metal coupling agent is introduced to form a covalently crosslinked MO-Si network. This imparts excellent hardness (>9H), high transparency (>90%), low CAH (<2°), wear resistance, and fingerprint resistance to the coating at an extremely low PDMS content (0.5-1.5wt%). The coating is suitable for surface protection in optoelectronic devices such as flexible OLEDs, solar cells, and ACEL devices.

[0071] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

Claims

1. A method for preparing a liquid-like coating based on dynamic phase separation, characterized in that: The following steps are involved: Step 1: Add the silicone resin and the hydroxyl-terminated linear PDMS to a volatile solvent, and process them sequentially through a homogenizer and an ultrasonic crusher to disperse the PDMS into small liquids to form an incompletely compatible mixed system; Step 2: slowly dropwise adding a metal coupling agent into the above-mentioned mixed system, stirring to cause a pre-crosslinking reaction between the metal coupling agent and the active groups of the silicone resin to obtain a coating solution; Step 3: Apply the coating liquid on the surface of the flexible substrate, let it stand to evaporate the solvent, eliminate the phase separation, and perform heat curing treatment to cross-link the silicone resin and the PDMS end and complete the MO-Si structure to obtain a liquid-like coating, where M is the metal element of the metal coupling agent.

2. The preparation method according to claim 1, wherein: Calculated by mass fraction, the organic silicone resin accounts for 50-80wt% of the coating liquid, the hydroxyl-terminated linear PDMS accounts for 0.5-1.5wt% of the coating liquid, the metal coupling agent accounts for 1.0-5.0wt% of the coating liquid, and the volatile solvent accounts for 15-45wt% of the coating liquid.

3. The preparation method according to claim 1, wherein: The organic silicone resin is a methoxysiloxane intermediate.

4. The preparation method according to claim 1, wherein: The molecular weight of the hydroxyl-terminated linear PDMS is 1000-100000 g / mol.

5. The preparation method according to claim 1, wherein: The metal coupling agent includes a combination of one or more of a titanate coupling agent, an aluminate coupling agent, and a zirconate coupling agent.

6. The preparation method according to claim 1, wherein: The titanate coupling agent includes a combination of one or more of tetrabutyl titanate, isopropyl titanate and isooctyl titanate; the aluminate coupling agent includes a combination of one or more of isopropyl aluminate and butyl aluminate; and the zirconate coupling agent includes isopropyl zirconate.

7. The preparation method according to claim 1, wherein: The volatile solvent includes anhydrous ethanol, isopropanol, methanol or low-polarity esters.

8. The preparation method according to claim 1, wherein: In step 3, the thickness of the liquid-like coating is 1-100µm.

9. The preparation method according to claim 1, wherein: In step 3, the temperature of the heat curing treatment is 25-200° C., and the time is 0.1-20 hours.

Citation Information

Patent Citations

  • Fluid-like interface, construction method and anti-pollution application thereof

    CN112063001A

  • Room-temperature-curing solvent-free anti-doodling coating

    CN113999613A

  • Preparation method of polymer-based molecular brush super-lubricating coating

    CN114769094A

  • Method for preparing self-roughening surface by polarity induced phase separation method and product thereof

    CN114874697A

  • Ultra-low adhesion coating with anti-sticking and self-oil-seepage characteristics as well as preparation method and application of ultra-low adhesion coating

    CN119192996A